High phospho‐histone H3 expression uniquely predicts favorable survival among four markers of cellular proliferation in colorectal cancer. Issue 5 (25th February 2021) - Koshino, Akira; Inoue, Satoshi; Sugimura‐Nagata, Akane; Nishiyama, Takeshi; Murakami, Hideki; Ito, Hideaki; Riku, Miho; Inoko, Akihito; Ebi, Masahide; Ogasawara, Naotaka; Tsuzuki, Toyonori; Kasugai, Kunio; et al.
Abstract : Colorectal cancer (CRC) is one of the most frequent gastrointestinal cancers worldwide, with high morbidity and mortality rates. Despite numerous attempts to identify prognostic markers for the CRC patients, the significance of the association of cellular proliferation markers with survival is controversial. Here we used immunohistochemistry to detect four markers of cellular proliferation expressed in primary CRC tissue specimens (n = 269) to assess their potential to serve as prognostic factors. CRC cells variably expressed phospho‐histone H3 (PHH3) (range, 0–76 per high‐powered field (HPF); median, 7 per HPF), cyclin A (CCNA) (range, 11.3–73.7%; median, 32%), geminin (GMNN) (range, 7.8–82.0%; median, 37.1%), and marker of proliferation Ki‐67 (MKI67) (range, 4.9–96.6%; median, 49.6%). Among them, patients with PHH3‐high (≥7 per HPF) tumors uniquely experienced significantly longer 5‐year survival than those with PHH3‐low (≤6 per HPF) (81.8% vs. 65.5%; P = 0.0047). Multivariable Cox hazards regression analysis identified PHH3‐high (hazard ratio, 0.54; 95% confidence interval, 0.31–0.92; P = 0.025) as potential favorable factors. PHH3 levels inversely associated with pT stage ( P < 0.0001) and were significantly and inversely associated with tumor diameter ( ρ = −0.314, P < 0.0001). These findings support the use of PHH3 immunohistochemistry for predicting the prognoses of patients with CRC.